Building Competitive Advantage from the Perspective of Store Atmosphere, Service Quality, and E-WOM - Jati Nugroho; Iwan Hermawan; Inayah, Inayah; Suharmanto, Suharmanto; Luqman Khakim (International Journal of Education, Vocational and Social Science, 2023)
The fashion business in the city of Semarang has very intense competition, so the uniqueness and excellence of the products offered to consumers becomes a challenge. This requires creativity, innovation, and the courage to try new products. The purpose of this study is to measure the effect of Store Atmosphere, Service Quality, and E-WOM (Electronic Word of Mouth) on Competitive Advantage. The problem of this research is "Building Competitive Advantage from the Perspective of Store Atmosphere, Service Quality, and E-WOM in UMKM fashion in Semarang City" after the COVID-19 pandemic. The population of this study was fashion MSMEs in Semarang City, with the number of samples used being 100 samples from the respondent population. The sampling technique used the purposive sampling method. This research technique uses two approaches: 1) Confirmatory Factor Analysis, on Structural Equation Modeling (SEM); and 2) Regression Weight on Structural Equation Modeling (SEM). The output of this study can make a positive contribution to UMKM fashion in an effort to be able to realize their business continuity, both in the form of managerial implication suggestions and formulation of scientific articles and measurement instruments. Managerial advice is aimed at the local government in formulating program policies to maintain the existence of entrepreneurs after the COVID-19 pandemic.